Improved water management through effective water users associations in Central Asia: Case of Kyrgyzstan - Kazbekov, Jusipbek S.; Abdullaev, Iskandar; Anarbekov, Oyture; Jumaboev, Kahramon (International Water Management Institute, 2007)
Continuous institutional changes in the rural sector in Central Asia have negatively affected the reforms and the development of other related sectors, e.g. the irrigation sector. Therefore, reforms in the irrigation sector have been carried out in an ever changing and uncertain environment. Institutional changes have so far been aimed the farm level that was formerly managed by collective and state farms. Replacement of relatively few collective farms by thousands of individual farming units has resulted in chaos and anarchy in water management at on farm level. Water Users Associations (WUAs) were introduced in Kyrgyzstan to better organize farm level water management. The key questions concerning WUAs in Kyrgyzstan at present are: Do they provide better service for farmers in delivering water? Do irrigation services result in good crop yields? Are they financially viable? In order to answer these questions, the irrigation performance of four WUAs located within one main canal area in Osh province of Kyrgyzstan were assessed for the period 2003-2005. The analysis indicates that in spite of intense international support, WUAs in the study area were performing relatively poorly on irrigation service provision. However, there are signs of improvement, such as increasing water productivity, reduced water use and improved financial sustainability. The Kyrgyz experience on transformation of on-farm level water management from collective farms to WUAs can provide good examples for neighboring countries, e.g. Tajikistan, Uzbekistan, where agricultural restructuring has only started recently.